FLOVERA: Smart and Sustainable Edible Packaging Innovation for Environmental Responsibility - Annisa Annisa; Armeina Mujtahidah; Azzahra Putri Efania; Muryani Anggita; Afryansyah Afryansyah (Jurnal Penelitian Medan Agama, 2025)
The increasing global demand for sustainable, eco-friendly, and intelligent food packaging has driven the development of biodegradable materials capable of not only reducing plastic pollution but also actively sensing food spoilage. This research presents the design and evaluation of an edible rice paper derived from Manihot esculenta (cassava) leaf fibers integrated with natural pH-responsive anthocyanin indicators from Clitoria ternatea (butterfly pea flower). The material exhibits visible color changes in response to pH variations associated with food decomposition, enabling real-time monitoring of food freshness. Mechanical, physicochemical, and colorimetric properties of the developed bio-film were systematically characterized. Results demonstrate that the film exhibits significant pH-sensitive color transformation, desirable mechanical strength, antioxidant activity, and rapid biodegradability when compared with conventional synthetic polymers. These findings support the potential of this material to serve as a green alternative to traditional plastic packaging, enhancing food safety while mitigating environmental impacts. This work contributes to sustainable packaging innovation and addresses critical challenges of plastic waste and consumer health risks linked to synthetic packaging materials.